Digitalisasi Manajemen Keuangan dan Investasi untuk Pemberdayaan Ekonomi Rumah Tangga PKK Desa Durian - Budiarti, Lina; Arninda, Arninda; Miftahul Sirat, Okta; Andriansyah, Andriansyah (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The economic empowerment program for the PKK Group in Durian Village aims to enhance members' capacity in financial management and investment through digitalization. This program equips PKK members with skills to effectively manage household finances, understand the importance of income diversification, and manage financial risks. Members are trained to use digital technology to record finances, create budgets, and independently analyze their financial situations. Through training and mentoring, members learn to use digital financial applications to help track expenses and income. Additionally, the program develops entrepreneurial and time-management skills, enabling PKK members to run small businesses independently and increase productivity. Results show a significant improvement in understanding; the average pretest score was 50, which increased to 83.25 on the posttest. Other success indicators include increased household income, the opening of brokerage accounts as an initial investment step, improved access to financial services, and enhanced economic welfare and household independence. This program is expected to be an initial step toward greater economic independence for families and inclusive local economic development in Durian Village. With digital technology adoption in financial management, Durian Village is anticipated to serve as a model of technology-based economic empowerment in rural areas.